Synthesis and Characterization of Isopropylidene Glycerol Acetate and Isopropylidene Glycerol Propanoate Compounds - Ridlo, Achmad; Choirunnisa, Lutfia; Rahmawati, Fani; Irunsah, Aslan; Ishartono, Bayu (Indonesian Journal of Chemical Studies, 2023)
Isopropylidene Glycerol Acetate (IGA) and Isopropylidene Glycerol Propanoate (IGP) as ester compounds using acetic and propanoic acids have been synthesized, characterized, and studied for their antibacterial properties. The IGA was synthesized from ethyl acetate (EtOAc) and 1,2-O-isopropyliden glycerol (IPG) with a mole ratio of 1:8 through a transesterification reaction. Meanwhile, the IGP was synthesized using ethyl propanoate (EP) with the same ratio and method as IGA. All materials in this study were identified using FT-IR, GC-MS, 1H-NMR, and 13C-NMR. The characterization results indicated that the compounds of EP, IPG, IGA, and IGP had been successfully formed and identified. It was also revealed that the compounds of EP, IPG, IGA, and IGP were successfully synthesized with yields of 37.72, 27.78, 70.11, and 63.83%, respectively. The antibacterial activity test revealed that neither IGA nor IGP inhibited the growth of Staphylococcus aureus or Escherichia coli at concentrations of 62.5; 125; 250; 500; and 1000 ppm. Therefore, it was asserted that ester compounds synthesized with short-chain carboxylic acids, such as propanoic and acetic acids, lacked antibacterial properties.